INDUSTRIAL LABOR ABSORPTION AND CHANGES IN THE ECONOMIC STRUCTURE OF COMMUNITY BASED ON EDUCATION - Zaima Hilmi; Sri Rahayu Budiani (JURNAL GEOGRAFI, 2022)
Kendal Regency has developed into one of the Special Economic Zones. The development is to become one of the new industrial areas to improve the economy of the community and the region. This is undoubtedly related to the hope of increasing employment so that it is also able to increase employment and improve the economy of the community and the region. However, the availability of labor is still dominated by elementary school graduates/equivalent, and the impact of industrial development on the regional economy has not been seen significantly. Therefore, this study aims to determine the relationship between industrial growth and employment based on the last education completed, the relationship between industrial growth and industrial GRDP growth, and strategies that can be taken to maximize employment. This study uses secondary data collected from the BPS, namely Kendal Regency in Figures and Central Java Province, and related regional regulations. The primary data available is insufficient for data needs requiring time-series data. This study uses a quantitative method with the Kendalls'tau b correlation test and multiple correlation test analysis methods. It uses the calculation of the elasticity of labor and the projection of labor absorption. The result is that 1) there is a relationship between industrial growth and employment based on the last education completed, 2) there is no relationship between industrial growth and GRDP growth in the industrial sector, and 3) the strategy that can be done to maximize employment is to improve quality human resources and promote industrial growth.Keywords: employment, education, GRDP, industry